TECHNOLOGY AND GENERATION Z SPIRITUALITY IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW WITH KEYWORD CO-OCCURRENCE MAPPING - Muallim, M. Nuri; Andryadi; Noviriani; Aulia, Nila; Adilla, Ulfa; Narti, Wiwin (Irfani, 2023)
Generation Z Indonesians, born between 1997 and 2012, navigate religious meaning-making inside an information environment in which TikTok, Instagram, prayer-reminder apps, and online da’wah communities have become primary spiritual venues. This study reviewed how the published literature has characterised that shift and where the evidence base remains uneven. A systematic literature review was conducted following the PRISMA 2020 protocol across the Scopus and SINTA databases, supplemented by Google Scholar hand-searching, with a search window from January 2014 to October 2023. Of 359 records identified, 287 remained after duplicate removal; title-and-abstract screening excluded 168, and full-text assessment excluded a further 67, leaving 52 articles for qualitative synthesis. Bibliometric mapping with VOSviewer produced a five-cluster keyword co-occurrence network around digital da’wah and platforms, Generation Z identity and community, Islamic education, digital risks, and literacy and ethics. Thematic distribution shifted noticeably across four year-bands: digital da’wah accounted for 44% of the 2014–2016 articles but only 21% of the 2022–2023 articles, while literacy and ethics grew from 12% to 13% and risks from 11% to 17%. A typological quadrant of fourteen digital practices placed Quran-reader apps, prayer-reminder apps, verified online kitab archives, webinar kajian, and digital muhasabah journals in the Adopt quadrant; TikTok short da’wah clips, Instagram preacher celebrities, and online hijrah communities in the Guarded Adopt quadrant; and unverified fatwa forums, algorithmic feed scrolling, and auto-play religious entertainment in the Defer quadrant. The synthesis suggests that Generation Z spirituality in Indonesia has become a hybrid practice in which institutional authority, peer affirmation, and platform affordances jointly shape religious experience.